Pengaruh Pemberian Zat Pengatur Tumbuh (Growtone) terhadap Pertumbuhan Sowang (Xanthostemon novaeguineense Valet.) - Leonardo Elisa Aisoi (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Sowang (Xanthostemon novaeguineense Valet.) is an endemic plant of Papua whose population is currently experiencing very high pressure due to overexploitation, and the morphological characteristics of Sowang are very difficult to develop generatively, it is necessary to make efforts to reproduce vegetatively. Vegetative propagation is an alternative that needs to be done, one of which is by cuttings. Research on the effect of giving growtone on Sowang's growth has been carried out from March to July 2020, at the Green House Laboratory of the Department of Biology, FMIPA, Cenderawasih University, Jayapura, Papua. This study aims to determine the effect of giving growtone with different doses, types of cuttings, and the interaction of these two factors on the growth of Sowang cuttings. This study used an experimental method with a factorial Completely Randomized Design (CRD) with two factors and three replications. Factor 1, growtone (D0: control, D1: 50 ppm, D2: 100 ppm, and D3: 150 ppm), and factor 2, the type of cuttings Sowang (S1: shoot cuttings and S2: stem cuttings). The results showed that different doses of growtone and the type of cuttings had a significant effect on the growth of Sowang cuttings. The dose of growtone 150 ppm and the type of stem cuttings gave the best results in increasing the growth of Sowang shoot cuttings.